Muslim sects and divisions : the section on Muslim Sects in Kitāb al-Milal wa 'l-niḥal /: the section on Muslim Sects in Kitāb al-Milal wa 'l-niḥal. (2013) - Shahrastānī, Muḥammad ibn ʿAbd al-Karīm, 1086?-1153
No abstract available